THEORETICAL BASIS FOR FORMING A MECHANISM FOR ENSURING INNOVATIVE DEVELOPMENT OF INDUSTRIAL ENTERPRISES (Development Service Industry Management, 2024)
The article explores the fundamental concepts related to the innovative development of industrial enterprises. A thorough analysis of the essence of innovation is carried out, key features of innovation activity are defined, and its role in the strategic development of enterprises is emphasized. Existing types of innovations are described, including technological, organizational, product, and marketing innovations. A classification of these types is provided based on approaches used within the scientific community of innovation management specialists. The theoretical foundations for studying the innovative development of industrial enterprises are examined, encompassing modern concepts, approaches, and models of innovation management.As a result of the research, a system of basic concepts was formed, and logical connections between them were established, which made it possible to develop a theoretical basis for further study. In particular, a scheme for the mechanism of ensuring innovative development of industrial enterprises in the country is proposed. This scheme includes the main stages, elements, and principles of functioning and is logically structured, making it a practical tool for implementing innovation strategies across enterprises of various scales.Innovative development is considered as a continuous process aimed at increasing the enterprise’s competitiveness in the market of goods and services, enhancing economic efficiency, increasing market share, and ensuring long-term competitive advantages. The importance of continuous innovation implementation, active employee involvement in innovative activities, and the creation of an internal environment conducive to the development of innovation culture within the enterprise is emphasized.
Keywords: industrial enterprise; innovative development; innovations; theoretical basis; mechanism; competitiveness